Efektivitas Twitter Sebagai Media Speak Up Korban Kekerasan Berbasis Gender - Tri Yuliningsih; Anggi Prihatiningsih (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Victims of gender-based violence got a significant increase each year, it can even double from the previous year. Cases of gender-based violence are often difficult to solve, due to the lack of reports and witnesses, especially from the victims themselves. It is not easy to express or speak up about incidents that have been experienced by victims of gender-based violence. Often victims are silenced and unable to express their psychological condition. However, there is a free voice media, namely social media, one of which is Twitter. In that media, many victims of gender-based violence expressed what they experienced, and received support and there was no silence. With this, the researcher conducted a research on the effectiveness of Twitter as a media to speak up, especially for victims of gender-based violence who often feel silenced. Researchers use quantitative methods to obtain objective data and generate generalizable arguments whether effective or not. The result of this study is that Twitter is effective as a medium for Speak Up victims of gender-based violence.